2013
DOI: 10.1111/cogs.12086
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Instructionally Oriented Theory of Example‐Based Learning

Abstract: Learning from examples is a very effective means of initial cognitive skill acquisition. There is an enormous body of research on the specifics of this learning method. This article presents an instructionally oriented theory of example-based learning that integrates theoretical assumptions and findings from three research areas: learning from worked examples, observational learning, and analogical reasoning. This theory has descriptive and prescriptive elements. The descriptive subtheory deals with (a) the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
370
5
17

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(404 citation statements)
references
References 149 publications
12
370
5
17
Order By: Relevance
“…The learning materials comprised a combination of instructional techniques that foster constructive engagement: worked examples (e.g., Renkl, 2014), self-explanation prompts (e.g., Chi, De Leeuw, Chiu, & Lavancher, 1994), and the possibility to compare and contrast the three examples (e.g., Alfieri, Nokes-Malach, & Schunn, 2013). The worked examples were adapted from a study by and instantiated the three models (M1, M2, and M3) within three different context stories (C1, C2, and C3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning materials comprised a combination of instructional techniques that foster constructive engagement: worked examples (e.g., Renkl, 2014), self-explanation prompts (e.g., Chi, De Leeuw, Chiu, & Lavancher, 1994), and the possibility to compare and contrast the three examples (e.g., Alfieri, Nokes-Malach, & Schunn, 2013). The worked examples were adapted from a study by and instantiated the three models (M1, M2, and M3) within three different context stories (C1, C2, and C3).…”
Section: Methodsmentioning
confidence: 99%
“…Under some circumstances this may be problematic, as existing knowledge is an important predictor of future learning (e.g., Schneider & Bullock, 2009). Thus, to constructively engage with learning materials, learners need basic knowledge on all to-be-learned core concepts, on which they can build, for example, by constructing principle-based self-explanations (Renkl, 2014), by devising well supported arguments (Noroozi, Weinberger, Biemans, Mulder, & Chizari, 2012), or by working out a comprehensive problem solution (Rummel & Spada, 2005). Such constructive, individual engagement is also the basis for effective interactive knowledge construction (Chi & Wylie, 2014).…”
Section: Disadvantages Of Knowledge Interdependencementioning
confidence: 99%
“…Working memory capacity might moderate the effects of different kinds of instructional support aimed at reducing working memory load. Instructional support through worked examples is assumed to be effective in reducing load in working memory (e.g., Renkl, 2014). The benefit of worked examples might be especially pronounced for learners with low working memory capacity (van Gog & Rummel, 2010).…”
Section: Aptitude Treatment Interactions In the Context Of Complex Lementioning
confidence: 99%
“…Therefore, we could be confident that effects (if any) would not be caused by differences in the content that was being presented.' ' We firstly hypothesized that for male and female secondary education students who have little if any knowledge of solving probability calculation problems, it would be effective to study video modeling examples with both a male and female model, because research has consistently shown that example-based learning is very effective and efficient for novice learners (Atkinson et al 2000;Renkl 2014;Sweller et al 2011;Van Gog and Rummel 2010).…”
Section: The Present Studymentioning
confidence: 99%